EVIDENCE FOR A NEW AD SYNDROME: REPORT OF A LARGE IRANIAN SIBSHIP WITH SEVERE MULTIPLE SYNOSTOSIS - D.D. Farhud (Tehran University of Medical Sciences, 1997)
An investigation was carried out on a young unrelated couple, both 29 years old, with two boys and three girls, 3 months to 8 years old. One boy and the mother were healthy, the other four children and the father were affected. The family, originally from the district of Nour, in northern Iran, near the Caspian Sea, was first counseled at the Genetic Clinic in Tehran in 1984. Several trips were made to the location in a period of five years, to examine this large family. The major anomalies in this family were brachyphalangia, elbow joint aplasia (humero - radial synostosis, 110 to 140°C), carpal/tarsal synostosis and talus/calcaneus fusion. All affected individuals present a fixation of the feet in supination position and because of partial synostosis (physis) of calcaneus and talus, walked on lateral side with the external cant of the foot. All deformities were studied by clinical examinations and radiological confirmations, on each affected individual.